2019
DOI: 10.1371/journal.pntd.0007382
|View full text |Cite
|
Sign up to set email alerts
|

Identification of divergent Leishmania (Viannia) braziliensis ecotypes derived from a geographically restricted area through whole genome analysis

Abstract: Leishmania braziliensis , the main etiological agent of cutaneous leishmaniasis (CL) in Latin America, is characterized by major differences in basic biology in comparison with better-known Leishmania species. It is also associated with a high phenotypic and possibly genetic diversity that need to be more adequately defined. Here we used whole genome sequences to evaluate the genetic diversity of ten L . braziliensis isolates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 67 publications
1
39
1
Order By: Relevance
“…This species is characterized by its ability to cause distinct forms of tegumentary leishmaniasis in humans (Jirmanus et al, 2012;Meireles et al, 2017) and animals (De Oliveira et al, 2013;Brilhante et al, 2019), and also for its variable infectivity, virulence, and response to anti-leishmanial therapy (Rego et al, 2018;Patino et al, 2019a). In addition, it is considered a zoonotic parasite circulating in a wide range of mammalian and vector host species (Kuhls et al, 2013;Roque and Jansen, 2014), characteristics that can contribute to the generation and maintenance of genetic diversity within the species (Cupolillo et al, 2003;Bruna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This species is characterized by its ability to cause distinct forms of tegumentary leishmaniasis in humans (Jirmanus et al, 2012;Meireles et al, 2017) and animals (De Oliveira et al, 2013;Brilhante et al, 2019), and also for its variable infectivity, virulence, and response to anti-leishmanial therapy (Rego et al, 2018;Patino et al, 2019a). In addition, it is considered a zoonotic parasite circulating in a wide range of mammalian and vector host species (Kuhls et al, 2013;Roque and Jansen, 2014), characteristics that can contribute to the generation and maintenance of genetic diversity within the species (Cupolillo et al, 2003;Bruna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The last genomic analysis used to evaluate the genetic variability among the genomes included in this study was associated with the identification of nucleotide-level variations (SNPs). Initially, we observed that the number of SNPs per genome in all the clades analyzed was low (≈1800 to ≈3700 SNPs) ( Figure 4A), compared with the results obtained for other Leishmania (Viannia) species, such as L. braziliensis, where the number of variants observed in clinical isolates from Brazil ranged from ≈96,000 to ≈132,000 SNPs [26], in clinical isolates from Colombia was approximately 18,000 (data in preparation), and in L. peruviana isolates was approximately 27,000 [21]. These results together with the relationship between the number of homozygous/heterozygous SNP sites (39.785/21.603), observed in this study (Table S3), indicate not only a considerable genetic differentiation among species belonging to the same subgenus (L. braziliensis, L. peruviana, and L. panamensis) but also substantially lower variation in terms of SNPs in L. panamensis.…”
Section: Discussionmentioning
confidence: 70%
“…Although the extensive literature has revealed intra-and interspecific genetic variability of some Leishmania species (mainly L. donovani, L. major, L. tropica) [23,30,41,42], little is known about the genetic variability of Leishmania (Viannia) species. The reported studies so far have focused on L. braziliensis, where the majority report consistent findings in describing its high intraspecific genetic diversity [16,26,43] even in cell populations isolated from a single L. braziliensis strain ("sub-strain") [44], while in L. panamensis the results are not yet concordant, probably for the molecular approaches used. While studies using MLST reveal extreme genetic homogeneity within L. panamensis [10], others using MLEE [5], sequencing of specific genes (Cytb/HSP70) [6], AFLP [13], or microsatellites [14], have reported a high intraspecific genetic diversity in this species.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our understanding of the genetics of diversification and hybridization in Leishmania is increasingly informed by the genomic revolution. Whole genome sequencing data of hundreds of isolates revealed the global 18 and local 19,20 genome diversity of the Old-World L. donovani species complex, although genome studies on New-World Leishmania species remain scarce and limited to a few isolates 2123 . Genome-scale analyses also provided strong evidence for genome-wide patterns of recombination in presumed clonal Leishmania species 2426 , including evidence of classical crossing over at meiosis 24 .…”
Section: Introductionmentioning
confidence: 99%